Cyclic loading of freshwater ice produced in the laboratory and sea ice collected in the Beaufort Sea with thermal microcracks, 2022-2023 ... - Murdza, Andrii; Schulson, Erland; Renshaw, Carl (NSF Arctic Data Center, 2023)
The combination of thinning ice, larger waves, and damage due to diurnal thermal cycling motivate the need to better understand the impact of flexing under the action of oceanic waves on the strength of thermally-cracked ice. To that end, new experiments were performed on freshwater, lab-grown ice and first-year natural sea ice. All experiments were conducted in the Ice Research Laboratory, Thayer School of Engineering, Dartmouth College. Freshwater ice was produced in the laboratory, while sea ice was collected in the Beaufort Sea. Both materials were cracked by thermal shocking and then subsequently cyclically flexed. Initially, the thermal cracks weakened both materials. When the cracked ice of either origin was cyclically flexed under fully reversed loading, its flexural strength, initially reduced by the stress-concentrating action of the cracks, recovered to the strength of non-cracked, non-flexed ice. When the cracked ice was cyclically flexed non-reversely, its strength recovered only partially. ...